A Peculiar Distribution of the Emerging Nematode Angiostrongylus cantonensis in the Canary Islands (Spain): Recent Introduction or Isolation Effect? - Natalia Martín-Carrillo; Carlos Feliu; Néstor Abreu-Acosta; Elena Izquierdo-Rodriguez; Roberto Dorta-Guerra; Jordi Miquel; Estefanía Abreu-Yanes; Aarón Martin-Alonso; Katherine García-Livia; María Antonieta Quispe-Ricalde; Jordi Serra-Cobo; Basilio Valladares; et al. (Animals, 2021)
Angiostrongylus cantonensis is an emerging zoonotic nematode recognized as the leading cause of eosinophilic meningitis in the word. After its discovery in China, it was recorded in 30 countries worldwide. Recently, it has expanded to new areas such as South America and it has been recently found in the Atlantic island of Tenerife (Canary Islands). In order to characterize the distribution of A. cantonensis in the Canary Islands, the lungs of 1462 rodents were sampled in eight islands of the archipelago over 13 years and were then analyzed for A. cantonensis. Remarkably, the parasite was detected only in Tenerife, in Rattus rattus (19.7%) and Rattus norvegicus (7.14%). They were concretely in the northern part of the island, which had a warmer and more humid climate than the south and main cities. The absence of this nematode in other islands with similar environmental conditions could be explained by an isolation effect or by a recent introduction of the parasite in the islands. Besides, the presence in Tenerife of the most invasive lineage of A. cantonensis reinforced the hypothesis of a recent introduction on this island. This study highlights the need to implement control measures to prevent the expansion to other areas in order to avoid the transmission to humans and other animals.